The amount of money Andrew starts with we set as X
X - 940 - 5/7(X - 940) + 240 = 2/9X
X- 5/7X -2/9X -940 +4700/7+240 = 0
4/63X = 200/7
4X = 1800
X = 450????
Can someone check my process because either I made a mistake during calculation or there's something wrong with the question. He can't start with 450 and spend 940.
This isn't a question that could be solved very easily.
We try to list equations:
G = 1/7(M+K+J)
M = 3/4(K+J)
J = 2/5K
Let's Plug in:
M = 3/4(7/5K) = 21/20K,
G = 1/7(21/20K+K+2/5K) = 1/7(49/20K) = 7/20K
K = K
J = 2/5K
M = 21/20K
G = 7/20K
Now we split all of that $168 into these four parts. 4 parts combined is 56/20K, and thus K original has 168*20/56 = $60. J original has 168*8/56 = $24
Now you can do the last step: $60 - $X = $24 + $X
Hopefully this proved to be helpful
OK, so I would set all the money he has at first as X, our variable.
X - 1/3X - 120 = 2/3X - 120 is what he has after sentence 1
1/3(2/3X-120)-120 = 2/9X - 160 is what he has after sentence 2
1/3(2/9X - 160) -120 = 2/27X - 520/3 is what he has after sentence 3, but since by this time he doesn't have any money left, we can infer than
2/27X - 520/3 = 0, thus 2/27X = 520/3.
Find X to get the answer.
We set all the marbles Fred has as X.
We can infer from the first sentence that: X - (1/4X+34) = 3/4X - 34 marbles is what Fred has after the first sentence
Now, 3/4X - 3/8(3/4x - 34) = 3/4X-9/32X+51/4 = 15/32X+51/4 is what he has after the second sentence
That suggests that 15/32X + 51/4 = 580, which means 15/32X = 2551/4, and find X to get the answer to the question.